Human Factors Shaping Cybersecurity Behavior in Work from Home Environment in Ugandan Universities - Atuhe Aarone Mike; Akampurira Paul; Richard Ntwari (INTERNATIONAL JOURNAL OF RESEARCH AND INNOVATION IN APPLIED SCIENCE (IJRIAS, 2026)
The shift to remote and hybrid work in Ugandan universities exposed new cybersecurity risks shaped by human motivation, cognitive load, and system usability challenges. As academic operations increasingly depended on digital platforms, understanding how individuals formed and enacted protective intentions within home-based work environments became critical. This study examined how human and contextual factors—including threat perception, copingappraisal, usability difficulty, cognitive load, and digital fatigue—influenced cybersecurity behaviour among staff working remotely in Ugandan universities. Guided by the Protection Motivation Theory (PMT) and supported by constructs from the Theory of Planned Behaviour (TPB), the research adopted a sequential explanatory mixed-methods design. The quantitative phase identified key motivational and contextual predictors, while the qualitative phase explored how fatigue, usability barriers, and environmental conditions shaped protective motivation. Integration was achieved through narrative comparison and joint display analysis. Quantitative findings revealed that coping confidence and usability difficulty were the most influential determinants of secure behaviour, whereas fatigue and cognitive load significantly undermined protective intentions. Qualitative narratives reinforced these patterns, highlighting themes of threat awareness, usability frustration, motivational fatigue, and uneven institutional support. The study concluded that cybersecurity behaviour in remote academic environments was driven by motivational and contextual dynamics rather than technical controls alone. Strengthening coping efficacy, reducing usability burdens, and addressing digital fatigue were identified as essential strategies for developing adaptive, human-centred cybersecurity interventions in higher education.
Keywords: Cybersecurity behavior; human factors; usability; digital fatigue; Theory of Planned Behavior; work from home.